Interfacial Role of Cesium in Prussian Blue Films. Issue 9 (9th July 2015) - Catalán, R.; Agrisuelas, J.; Cuenca, A.; García-Jareño, J. J.; Roig, A. F.; Vicente, F.
Abstract : The simultaneous measurement of current, mass, motional resistance and absorbance magnitudes allows the electrochemical cation insertion process to be explained during successive voltammograms around the Prussian Blue ⇄ Everitt's Salt system in CsCl aqueous acid solutions. Two different ways for the entrance of cesium to the porous structure of Prussian Blue have been observed. Firstly, Cs + is spontaneously absorbed as CsCl into the interstitial cluster of water of the channels formed by the Fe(II)low spin −CN−Fe(III)high spin structural units of the crystal. This chemical absorption involves a spontaneous substitution of inner water molecules of the interstitial water cluster. Finally, Cs + can act as a counter-ion during electrochemical stabilization process of Prussian Blue by means of successive voltammograms.